A critical review of corrosion characteristics of additively manufactured stainless steels. (17th November 2021) - Laleh, Majid; Hughes, Anthony E.; Xu, Wei; Gibson, Ian; Tan, Mike Y.
ABSTRACT: Additive manufacturing (AM) is associated with a sequence of rapid heating and cooling cycles along with large temperature gradients, developing complex thermal histories which have direct influence on resultant microstructures. Such a dynamic and far-from-equilibrium process leads to distinct microstructural features that are expected to cause changes in the corrosion characteristics of AM stainless steels. Currently such changes are not well understood, consequently inconsistencies and disagreements are frequently found in the literature on the corrosion behaviour of AM stainless steels. This paper performs a critical review of corrosion characteristics of AM stainless steels by assessing the effects of their unique microstructural features on corrosion behaviour, with particular focus on new corrosion phenomena and selected critical forms of localised corrosion including pitting corrosion, erosion-corrosion, intergranular corrosion, fatigue corrosion, and stress corrosion cracking. Discussion on the mechanisms of these corrosion phenomena and behaviour, as well as major influencing factors, are undertaken, leading to recommendations and suggestions for future development of AM stainless steels for various corrosive conditions.